Physical and thermal characterization of platinum tin dioxide based ceramic for gas sensing - Mas'ut, Aiza Masyati (2014)
Semiconducting metal oxide such as tin dioxide (SnO2) is widely utilized for sensing reducing gases such as Hydrogen (H2) and Carbon Monoxide (CO). Gassensor characteristics such as sensitivity, selectivity, response time and recovery time are often reported to be improved for the sensor with Platinum-catalyst than without the Platinum-catalyst. Thus, in this study, Platinum (Pt) up to 10 wt.% is added to SnO2 via solid state route and sintered at various temperatures. The material will further analyzed for thermal properties such as thermal diffusivity and thermal conductivity, as well as structural properties such as phase and crystallinity, microstructure, density-porosity, mean particle size and specific surface area. The gas sensor characteristics were studied in air, H2 and CO, respectively using two-probe method between 150 to 450 °C while the thermal properties of the Pt-SnO2 ceramic was studied using Laser Flash Analyzer from room temperature up to 400 °C. The microstructure of the sensor element was studied using X-Ray Diffractometer (XRD), Surface Analyzer, Scanning Electron Microscope (SEM) and density-porosity measurements. The mean particle size and specific surface area of the SnO2 powder performed by BET method were 0.12 μm and 7.5 m2g-1, respectively, and those of the Pt powder were 0.8 μm and 3.5 m2g-1.The density (porosity) of the samples increases (decreases) with sintering temperature and Pt loading. The phase composition analyzed by XRD, pointed out that all samples were tetragonal cassiterite polycrystalline in nature and there was no impurity phases in Pt-SnO2 system other than SnO2 and Pt phases. SEM micrographs showed that samples were assembled by lots of small spherical grains with voids and pores among them. Samples sintered at higher temperature yielded larger average grain size. As 0.5 wt.% Pt is introduced to pure SnO2 sample, the average grain size was decreased but the doped samples grew in grain size as Pt loading was further increased. The thermal diffusivity is increased with the increasing size of grain, at higher sintering temperature and with increasing of Pt loading. Samples with larger grain size also have larger room temperature thermal conductivities. All samples show a decrease in resistance either in air or gases with an increase in operating temperature. The resistance in air for the doped samples showed a higher resistance than the undoped SnO2 sample over the operating temperature. The resistance of the doped samples also increased with an increase in Pt doping in SnO2. The resistance of all samples in both H2 and CO gases decreases with temperature over the operating temperature. The undoped SnO2 sample was sensitive to all the test gases but the sensitivity value was very poor. The maximum sensitivity of undoped SnO2 was obtained at 400 oC. It was found that the optimum operating temperature for H2 and CO sensing in air was 300 and 200 oC, respectively, and the optimum composition for both gases was 0.5 wt.% Pt -SnO2 sample. Sample with 0.5 wt.% Pt loading also show good selectivity to H2 and CO at different temperature. The response and recovery times were greatly influenced by material composition, H2 concentration and H2 flow rate. In summary, the gas sensing process is strongly related to the surface reactions. Doped samples showed better gas response than the undoped sample due to the “spill over effect”. High surface areas (small grain size) with mesoporous structure produced by 0.5wt.%Pt-SnO2 sample provides large reaction contact area between gas sensing materials and target gases, thus contribute to the enhancement of the gas sensor characteristics. As for the thermal diffusivity and thermal conductivity of the SnO2-based samples, grain size and density-porosity effects play a major role in determining the properties where the values were in the range of 2.78 - 3.22 ×10-6 m2s-1and 3.93 - 4.87 Wm-1K-1, respectively.